2014
DOI: 10.1186/preaccept-1789442694116144
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a subtype C avian metapneumovirus circulating in Muscovy ducks in China

Abstract: Subtype C avian metapneumovirus (aMPV-C), is an important pathogen that can cause egg-drop and acute respiratory diseases in poultry. To date, aMPV-C infection has not been documented in Muscovy ducks in China. Here, we isolated and characterized an aMPV-C, designated S-01, which has caused severe respiratory disease and noticeable egg drop in Muscovy duck flocks in south China since 2010. Electron microscopy showed that the isolate was an enveloped virus exhibiting multiple morphologies with a diameter of 20-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
(56 reference statements)
1
1
0
Order By: Relevance
“…The pathogenicity of AMPV for the chicken’s oviduct was shown to be higher in the uterus than in the magnum and isthmus, which suggests a different susceptibility of epithelial cells for the three parts of the chicken’s oviduct [ 62 ]. In China, a similar disease picture was reported in egg-laying Muscovy ducks [ 63 ]. In Italy, longitudinal studies and sporadic samplings indicated that most pullet flocks get infected with AMPV before the laying begins [ 64 ].…”
Section: Viral Infections That Induce Ovary And/or Oviduct Diseasesupporting
confidence: 64%
“…The pathogenicity of AMPV for the chicken’s oviduct was shown to be higher in the uterus than in the magnum and isthmus, which suggests a different susceptibility of epithelial cells for the three parts of the chicken’s oviduct [ 62 ]. In China, a similar disease picture was reported in egg-laying Muscovy ducks [ 63 ]. In Italy, longitudinal studies and sporadic samplings indicated that most pullet flocks get infected with AMPV before the laying begins [ 64 ].…”
Section: Viral Infections That Induce Ovary And/or Oviduct Diseasesupporting
confidence: 64%
“…Since 2011, Muscovy ducks have been affected by a severe disease with egg‐drop and ovary–oviduct symptoms, which has been spreading through farms in South China. At first, the causative agent of this disease was suspected to be subtype C avian metapneumovirus (Sun et al., ). However, despite the implementation of a vaccine against this pathogen, the disease continued to spread.…”
Section: Introductionmentioning
confidence: 99%